Grammar Teaching: A Bibliographical Review (2010-2021); [Enseñanza de la Gramática: Una Revisión Bibliográfica (2010-2021)] - Rubio-Manriquez, M; Contreras-Torregrosa, M (Universidad de Playa Ancha de Ciencias de la Educacion, 2023)
This article presents a synthesis of a literature review on the teaching of Spanish grammar during the period 2010-2021. Through an integrative review, 41 articles were identified, analyzed along three axes: a) teaching grammar in history, b) teaching Spanish grammar as a mother tongue and c) teaching Spanish grammar as a foreign language. In the first, it is shown that the teaching of school grammar from the late nineteenth century to the mid-twentieth century adopted a prescriptive approach. In the second, two lines of work were identified: the characterization of syntactic development in different groups of students and the treatment of grammar in order to support the acquisition of syntactic structures. In the latter axis, research focused on difficulties in the development of the verbal system and error analysis. It is concluded that more research and didactic proposals oriented to the configuration of an educational linguistics proper are required. © 2023 Universidad de Playa Ancha de Ciencias de la Educacion. All rights reserved.